2016
DOI: 10.1039/c6ce00396f
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of polyiodide chains via anion⋯anion interactions: experiment and theory

Abstract: In tyrosinium polyiodide hydrate, cations and anions aggregate in layers. The cation layers are stabilized by classical hydrogen bonds. The anionic part of the structure consists of parallel infinite polyiodide strands; the distance pattern along these chains suggests the presence of smaller subunits I 3 − , I 2 and I − . Comparative calculations for small fragments and longer chains in frozen geometries indicate that this unexpected arrangement is favoured by local stabilizing anion⋯anion interactions and par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 44 publications
3
42
0
Order By: Relevance
“…In the widely used QTAIM theory, [193] this kind of analysish as been deeplyd eveloped for 1ðr)t oc haracterize many aspects that this functione xhibits in atoms,m olecules and their interactions. [212,213] Thus, in the polyiodide chains of the crystal structure of tyrosinium polyiodide hydrate (Figure 10 b), iodines are distinguished from iodides by the type of CPs found in their interactions with surrounding atoms. Hence, the study of the topological critical points (CP) of r 2 1 r ðÞhas indicated that charge concentration (CC) and charge depletion (CD) sites found in the valence shell of atoms are drivingg eometric preferences of molecules in the solid state.…”
Section: Chemical Bonding Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…In the widely used QTAIM theory, [193] this kind of analysish as been deeplyd eveloped for 1ðr)t oc haracterize many aspects that this functione xhibits in atoms,m olecules and their interactions. [212,213] Thus, in the polyiodide chains of the crystal structure of tyrosinium polyiodide hydrate (Figure 10 b), iodines are distinguished from iodides by the type of CPs found in their interactions with surrounding atoms. Hence, the study of the topological critical points (CP) of r 2 1 r ðÞhas indicated that charge concentration (CC) and charge depletion (CD) sites found in the valence shell of atoms are drivingg eometric preferences of molecules in the solid state.…”
Section: Chemical Bonding Analysismentioning
confidence: 99%
“…Hence, the study of the topological critical points (CP) of r 2 1 r ðÞhas indicated that charge concentration (CC) and charge depletion (CD) sites found in the valence shell of atoms are drivingg eometric preferences of molecules in the solid state. [214] Furthermore, the intersection of the gradient vector fields of 1 r ðÞ and V r ðÞ has shown to help to understand the counterintuitive assembling of anion-anion and cation-cation aggregates, [215][216][217][218] pointing out the regions of space that are involved in local attractive electrostatic interactions in hydrogen [219] and halogen [212] bonding. [212,213] Thus, in the polyiodide chains of the crystal structure of tyrosinium polyiodide hydrate (Figure 10 b), iodines are distinguished from iodides by the type of CPs found in their interactions with surrounding atoms.…”
Section: Chemical Bonding Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Different theoretical approaches to study bonds in PIs exist, for example,calculations of the potential energy surface and bond order, [5] energy decomposition analysis (EDA), [6] analysis of the electron density and its Laplacian at bond critical points (BCP), [7] theelectron localization function, and the one-electron potential. [8] Furthermore,t he energy den-…”
mentioning
confidence: 99%